Travel Decisions: The Effect of Facebook Posts According to Gender - Ramos, Dina; Au-Yong-Oliveira, Manuel; Flores Jr., Rogelio; Malta, Ana; Costa, Carlos (Journal of Reviews on Global Economics, 2019)
Supporting Ferreira (2012), Mariani et al. (2016) and Rodríguez‐Vázquez et al. (2017), it is essential to study the impact of social networks in the tourism sector, as they constitute innovative practices, with a substantial number of users involved. We aimed to understand the impact that Facebook posts have on the choice of a tourist destination. We thus prepared an online questionnaire, which obtained 361 answers, from a convenience sample involving international contacts of the authors, from 22 countries. This study revealed that men are much more influenced by Facebook posts, related to travel destinations, than women. We did inferential statistics, namely the chi square test, and we conclude that there does seem to be an association between gender and the influence of Facebook posts, at the 0.1% level. This may mean that tourism marketing firms may need to adjust their approach. We suggest that future research investigate further this phenomenon.